Arts as a driver of agility: A mixed-method inquiry - M. Janani; V. Vijayalakshmi (Acta Psychologica)
The Fifth Industrial Revolution focuses on building sustainability by balancing human factors (such as resilience and well-being) and technological innovations. This era of evolving, diverse, and turbulent business environments demands an agile workforce. However, scholars note a deficit in initiatives to boost agility due to the lack of evidence-based agility training practices. This study aims to design and test novel training using ‘arts’ to boost employee agility. An Intermodal Arts-Based Intervention (IABI) integrating visual arts, music, movement, and theatre was designed for this purpose. We employed a mixed-method inquiry in two stages to test its effect. Study 1, a quasi-experimental study (N = 139), was conducted for five sessions (15 h) across five weeks. It examined the difference in Workforce agility between the intervention and control groups. Results showed a significant increase in agility for participants in the intervention group. As a follow-up, Study 2, a focused group discussion (N = 13), was conducted after six months to understand its long-term outcomes on employees' affect, behavior, and cognition. The result revealed that agile behaviors were sustained by an increased ‘openness to experience’ and ‘socio-cognitive mindfulness’. This finding advances the agility literature by proposing a conceptual model for future scholarly inquiry and delineating the behavioral indicators of agility. In addition, this study is one of the first to design and test an employee-centric intervention to foster agile behaviors. The implications elaborate the use of IABI to establish a strengths-based employee development approach, such that firms aspiring to leverage a change-ready human capital can adopt the empirically tested intervention.